2013
DOI: 10.1016/j.ajo.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Macular Ganglion Cell/Inner Plexiform Layer Measurements by Spectral Domain Optical Coherence Tomography for Detection of Early Glaucoma and Comparison to Retinal Nerve Fiber Layer Measurements

Abstract: Purpose To evaluate the performance of ganglion cell/inner plexiform layer (GC/IPL) measurements with spectral-domain optical coherence tomography (Cirrus HD-OCT) for detection of early glaucoma and to compare results to retinal nerve fiber layer (RNFL) measurements. Design Cross-sectional prospective diagnostic study. Methods Fifty-nine glaucoma eyes (47 subjects) (mean deviation >–6.0dB) and 91 normal eyes (52 subjects) were enrolled. Patients underwent biometry and peripapillary and macular OCT imaging.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
90
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(104 citation statements)
references
References 40 publications
9
90
0
4
Order By: Relevance
“…In our study, we found that the mean thicknesses of RNFL and GC-IPL in both the glaucoma groups were thinner, as expected, compared with the normal C group. These results are consistent with those of previous studies (27,28) . The CCT values were found to be significantly thinner in the NTG group than in the other groups (p<0.05).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In our study, we found that the mean thicknesses of RNFL and GC-IPL in both the glaucoma groups were thinner, as expected, compared with the normal C group. These results are consistent with those of previous studies (27,28) . The CCT values were found to be significantly thinner in the NTG group than in the other groups (p<0.05).…”
Section: Discussionsupporting
confidence: 83%
“…Motion process and contrast sensitivity are parts of these visual processes (26) . In addition, ATD patients may have structural defects in the magnocellular visual pathway even in the absence of plaques and neurofibrillary tangles in these brain areas (27) . In our study, we found that the mean thicknesses of RNFL and GC-IPL in both the glaucoma groups were thinner, as expected, compared with the normal C group.…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with the conclusion of Cennamo et al [20] that inferior GCC (AUC = 0.792) and mean GCC thickness (AUC = 0.742) are the best parameters to discriminate initial glaucomatous changes before the onset of VF losses. Other authors, however, have reported that average cpRNFL measurements are superior to global GCIPL measurements for the detection of early glaucoma, but regional GCIPL measurements (minimum and inferior temporal GCIPL) performed as well as regional cpRNFL measurements (inferior quadrant) [21] . This is consistent with the fact that the inferior rim is the most common site of glaucomatous damage [22] .…”
Section: Discussionmentioning
confidence: 93%
“…Several studies have shown SDOCT mGCC measurements to have similar ability to detect glaucoma as cpRNFL (Schulze et al, 2011;Tan et al, 2009), with similar findings also observed using mGCIPL measurements (Akashi et al, 2013;Jeoung et al, 2013;Kotowski et al, 2012;Mwanza et al, 2012;Nouri-Mahdavi et al, 2013). Mzanwa and colleagues recently demonstrated average mGCIPL thickness to have excellent ability to differentiate healthy and glaucomatous eyes, with an AUC of 0.935, which was almost identical to the AUC of cpRNFL of 0.936.…”
Section: Imaging the Maculamentioning
confidence: 55%